The Mindanao State University an institutional study - Bulanti, Sabdani Jailani 1927- (s.n.], 1971)
This paper aims to make an institutional study of the Minadanao State University through its objectives, organizational structure, curriculum, staffing, physical plant, budget and capital outlay, and characteristics of students. It also describes the relation of the variables to the institutional objectives and ways to which these are achieved.